Caffeine enhances antitumor T-cell activity by suppressing kynurenine pathway in colorectal cancer - Yuechen Liu; Zhengyu Liu; Yating Hu; Yunyan Ling; Shunjie Qing; Yang Liu; Yizhi Zhan; Zhiyong Shen; Yuan Fang; Haijun Deng (Nature Communications)
Abstract Colorectal cancer (CRC) is a leading global health issue, ranking third in incidence and second in cancer mortality. Immunotherapy, effective mainly in mismatch repair-deficient CRC, may benefit from dietary interventions. This study investigates caffeine’s potential to boost programmed death-1 (PD-1) immunotherapy efficacy in CRC, revealing that caffeine significantly reduces tumor growth, extends survival, and enhances CD8+ T cell activity in CRC by suppressing kynurenine pathway. Mechanistically, caffeine decreases kynurenine via the Krüppel-like factor 4 (KLF4)- Collagen type XII alpha 1 (COL12A1)- Mitogen-Activated Protein Kinase (MAPK)-Indoleamine 2,3-dioxygenase 1 (IDO1) axis, mitigating CD8+ T cell exhaustion. Combining caffeine with PD-1 therapy further prolongs survival, highlighting the value of integrating nutritional strategies into cancer treatment to improve outcomes and broaden therapeutic options. Here, we show caffeine can enhance PD-1 immunotherapy in CRC by suppressing kynurenine pathway, suggesting its potential as an adjunctive dietary therapy.